Indikator Makroekonomi dalam Perspektif Sentimen Media Massa Internasional di Negara ASEAN - Sukmana, Eman; Musdalifah, Musdalifah; Amaludin, Bakhtiar; Nurcahyo, Anton (UI Scholars Hub, 2022)
This study was conducted to analyze the effect of international mass media sentiment on macroeconomic indicators in five ASEAN countries, namely Indonesia, Malaysia, Thailand, Singapore, and Brunei Darussalam. The purpose of this study is to develop a macroeconomic forecast model based on the analysis of macroeconomic indices and international sentiment that combines GDELT and World Development Indicators (WDI) data. The research result states that each economic index variable has a correlation with the news sentiment variable. The indicators most correlated with the news sentiment variable were Current Account Balance (CAB) (0.777628), Foreign Direct Investment (FDI) (0.727840), and Inflation (-0.223941). Therefore, economic policymakers (governments of each country) and market participants rely on a variety of models that incorporate soft information that includes subjective measures of attitudes about current and future economic conditions.